2016
DOI: 10.1097/md.0000000000004898
|View full text |Cite
|
Sign up to set email alerts
|

Delayed regaining of gait ability in a patient with brain injury

Abstract: Background:Little is known about delay in regaining gait ability at a chronic stage after brain injury. In this study, we report on a single patient who regained the gait ability during 2 months of intensive rehabilitation starting 2 years after a brain injury.Methods and results:A 40-year-old male patient diagnosed with viral encephalitis underwent comprehensive rehabilitation until 2 years after onset. However, he could not even sit independently and presented with severe physical deconditioning and severe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This is in agreement with previous studies (Teasdale et al, 1979;Authier et al, 1995) suggesting that there is a plausible effect of age and functional recovery, as youth plays a prominent factor in neuroplasticity following brain injury (Uswatte and Taub, 2010;Rutović et al, 2019). Additionally, other studies have shown that, depending on the severity of spasticity, some patients might demonstrate significant gait recovery levels (e.g., increased walking velocity) while other might show minimal improvements (Knutsson and Richards, 1979;Kuhtz-Buschbeck et al, 2003;Watson and Hitchcock, 2004;Tilson et al, 2010;Jang and Kwon, 2016;Marque et al, 2019), as observed postoperatively in SP1. Even though the joint kinematic parameters of the lower limbs in SP1 didn't show outstanding improvements over time, at 12 months postoperatively the patient was able to ambulate comfortably with a cane; no longer relying on a wheelchair.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with previous studies (Teasdale et al, 1979;Authier et al, 1995) suggesting that there is a plausible effect of age and functional recovery, as youth plays a prominent factor in neuroplasticity following brain injury (Uswatte and Taub, 2010;Rutović et al, 2019). Additionally, other studies have shown that, depending on the severity of spasticity, some patients might demonstrate significant gait recovery levels (e.g., increased walking velocity) while other might show minimal improvements (Knutsson and Richards, 1979;Kuhtz-Buschbeck et al, 2003;Watson and Hitchcock, 2004;Tilson et al, 2010;Jang and Kwon, 2016;Marque et al, 2019), as observed postoperatively in SP1. Even though the joint kinematic parameters of the lower limbs in SP1 didn't show outstanding improvements over time, at 12 months postoperatively the patient was able to ambulate comfortably with a cane; no longer relying on a wheelchair.…”
Section: Discussionsupporting
confidence: 91%
“…[4][5][6][7][8][9] As a result, detailed knowledge of gait could aid in the recovery of gait ability in stroke patients. [10,11] Gait requires coordination of various brain functions related to motor sensory, execution, attention, and visuospatial functions to achieve stepping movements, adequate leg and trunk muscle power and tone, maintenance of equilibrium, and interlimb coordination. [1,[12][13][14] Recent studies have reported that stroke patients regained their gait ability after the gait recovery phase of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Gait function is more likely to recover than hand function because leg motor function is less dependent on the lateral corticospinal tract (CST) than hand function [4–9] . As a result, detailed knowledge of gait could aid in the recovery of gait ability in stroke patients [10,11] . Gait requires coordination of various brain functions related to motor sensory, execution, attention, and visuospatial functions to achieve stepping movements, adequate leg and trunk muscle power and tone, maintenance of equilibrium, and interlimb coordination [1,12–14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the association between the neural tracts related to walking and gait recovery in stroke pa-J KPT tients. [21][22][23][24][25] However, little is known about characteristics of spatio-temporal and kinematic parameter of gait according to the injury aspect of the descending motor pathway by stroke. In this study, using a three-dimensional gait analysis and DTT, we investigate characteristics of recovered gait pattern according to the injury aspect of the CST, CRP, and VST in a patent with a chronic stroke.…”
Section: Introductionmentioning
confidence: 99%